Avaliação do equilíbrio e distribuição de pressão plantar em crianças com paralisia cerebral submetidas ao tratamento de toxina botulínica tipo A e fisioterapia - SILVA, Daniela Lima (2022)
Objective: To evaluate changes in lower limb muscle spasticity, distribution of contact area and plantar pressure, and COP variables after application of Botulinum Toxin type A (BoNT A) and physical therapy. Materials and Methods: Clinical trial, including 5 children with spastic diparetic Cerebral Palsy who received BoNT-A injection in lower limbs and associated physiotherapeutic treatment (up to 60 days post-BoNT-A). Anthropometric data (height, weight, age), functional capacity using the Gross Motor Function Classification (GMFCS), muscle tone using the Modified Ashworth Scale (MAS), static balance using the COP variables (stabilometry) and the distribution of pressure and plantar area by means of baropodometry. Results: Differences were identified in the parameters of the spasticity of the adductor muscles of the right hip (1.60±0.41 pre-therapy; 1.00±0.70 30 days post-therapy; t = 3.2; p= 0.032 ), right hamstrings (1.70±0.83 pre-therapy; 1.00±0.70 30 days post-therapy; t= 3.5; p=0.024 and 0.80±0.83 60 days post- therapy; t=9.0, p=0.0008) and left (1.50±0.50 pre-therapy; 0.80±0.44, 30 days post-therapy; t=3.5; p=0.024 and 0.60±0.54 60 days after therapy; t=9.0, p=0.0008 ) and in the distribution of mean plantar pressures in the forefoot (0.569±0.195 Kpa(r) pre therapy; 0.379±0.113 Kpa(r) ) 30 days post-therapy; t=3.90 p=0.017) and left midfoot (0.046±0.039 Kpa(r) pre-therapy; 0.112±0.080 Kpa(r) 30 days post-therapy; t=3.302; p =0.029). Final considerations: Our results suggest that short-term physical therapy associated with the application of BoNT-A provide a reduction in the spasticity of the proximal muscles of the lower limbs and improve the distribution of mean plantar pressures. However, they do not improve the static balance of children with spastic diparetic CP. Further research, with a longer period of physical therapy, is needed to confirm our findings.